The effect of low HER2 expression on treatment outcomes in metastatic hormone receptor positive breast cancer patients treated with a combination of a CDK4/6 inhibitor and endocrine therapy: A multicentric retrospective study - SARI, MURAT (My University, 2023)
Background: CDK4/6 inhibitors combined with endocrine therapy have significantly improved treatment outcomes for metastatic hormone receptor-positive (HR+) breast cancer patients. However, the impact of low HER2 expression on treatment response and progression-free survival (PFS) remains unclear. Methods: This multicenter retrospective study included 204 HR+ breast cancer patients treated with a combination of CDK4/6 inhibitor and endocrine therapy. HER2-zero disease was detected in 138 (68%) and HER2-low disease in 66 (32%) patients. Treatment-related characteristics and clinical outcomes were analyzed, with a median follow-up of 22 months. Results: The objective response rate (ORR) was 72.7% in the HER2 low group and 66.6% in the HER2 zero group (p = 0.54). Median PFS was not significantly different between the HER2-low and HER2 zero groups (19 months vs.18 months, p = 0.89), although there was a trend toward longer PFS in the HER2-low group for first-line treatment (24 months progression-free survival rate 63% vs 49%). In recurrent disease, the median PFS was 25 months in the HER2-low group and 12 months in the HER2-zero group (p = 0.08), while in de novo metastatic disease, the median PFS was 18 months in the HER2-low group and 27 months in the HER2-zero group (p = 0.16). The order of CDK4/6 inhibitor use and the presence of visceral metastasis were identified as independent variables affecting PFS. Conclusion: Low HER2 expression did not significantly impact treatment response or PFS in HR+ breast cancer patients treated with a CDK4/6 inhibitor and endocrine therapy. Because of the conflicting results in the literature, further prospective studies are needed to evaluate the clinical significance of HER2 expression in HR+ breast cancer.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Cerrahi Tıp Bilimleri; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Surgery Medicine Sciences; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; CERRAHİ; ONKOLOJİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; SURGERY; ONCOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Cerrahi; Kanser Araştırmaları; Surgery; Cancer Research; breast cancer; HER2-Low; hormone positive; palbociclib; ribociclib